Brazilian experts' consensus on the treatment of infantile epileptic spasm syndrome in infants - Letícia Pereira de Brito Sampaio; Adélia Maria de Miranda Henriques-Souza; Mariana Ribeiro Marcondes da Silveira; Lisiane Seguti; Mara Lúcia Schmitz Ferreira Santos; Maria Augusta Montenegro; Sérgio Antoniuk; Maria Luíza Giraldes de Manreza (Arquivos de Neuro-Psiquiatria, 2023)
Background Infantile epileptic spasms syndrome (IESS) is a rare but severe condition affecting children early and is usually secondary to an identifiable brain disorder. It is related to psychomotor deterioration in childhood and epilepsy in adult life. Treatment is challenging as infantile spasms may not respond to most antiseizure medication, and relapse is frequent.